2018
DOI: 10.1038/s41598-018-22540-1
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Phylogenomics and Putative Pathogenicity Genes of Pythium insidiosum by Oomycete Genome Analyses

Abstract: Pythium insidiosum is a human-pathogenic oomycete. Many patients infected with it lose organs or die. Toward the goal of developing improved treatment options, we want to understand how Py. insidiosum has evolved to become a successful human pathogen. Our approach here involved the use of comparative genomic and other analyses to identify genes with possible functions in the pathogenicity of Py. insidiosum. We generated an Oomycete Gene Table and used it to explore the genome contents and phylogenomic relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 66 publications
3
68
0
Order By: Relevance
“…No Pythium RXLR effector has been previously identified despite the numerous reports of RXLRs in their phylogenetically close species [21,22,23,24]. Here we developed a de novo identification method with stringent threshold to screen RXLR candidates in 9 Pythium species (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No Pythium RXLR effector has been previously identified despite the numerous reports of RXLRs in their phylogenetically close species [21,22,23,24]. Here we developed a de novo identification method with stringent threshold to screen RXLR candidates in 9 Pythium species (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The genome sequences of H. arabidopsidis [28], Ph. vexans [22], P. aphanidermatum [22], P. arrhenomanes [22], P. irregulare [22], P. iwayamai [22], P. oligandrum [39], P. periplocum [39], P. ultimum [21], P insidiosum [23], P. guiyangense [24], S. parasitica [40], P. tricornutum [41], T. pseudonana [42], S. cerevisiae [43], S. sclerotiorum [44], U. maydis [45], P. graminis [46], B. cinerea [47], C. elegans [48], M. hapla [49], E. coli [50], E. amylovora [51] and Ca L. asiaticus [52] were obtained from the National Center for Biotechnology Information (NCBI, https://www.ncbi.nlm.nih.gov/). Detailed genomic information of all species is listed in S7 Table.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we performed an in vitro susceptibility assay and showed that all 27 P. insidiosum strains tested were susceptible to disulfiram. In addition, we identified some putative target enzymes in the genome of P. insidiosum (27,28) and initially assessed a potential inhibitory mechanism of disulfiram against the pathogen by homology modeling, molecular docking, and biochemical analyses.…”
mentioning
confidence: 99%